An Anthropological Study on Household Infrastructure of Displaced Village (Journal of Informatics Education and Research, 2024)
Displacement refers to the intentional relocation of people from their homes to a new place for rehabilitation and reintegration purposes. The process involves consulting with local authorities, international organizations, and leaders of displaced groups to ensure safety and dignity during the relocation. Conservation activities during displacement may also impact land use patterns, local ecosystems, and economies in the affected areas. Community displacement can lead to the destruction of important infrastructure like schools, hospitals, and roads. It also affects individual homes, necessitating the creation of new infrastructure to support the displaced population. This can disrupt daily life and result in the loss of essential services. Rehabilitation efforts involve building new structures, providing transportation and maintenance, and often result in the loss of cultural heritage and social networks. This study studies the impact of displacement on personal infrastructure changes in families affected by displacement and rehabilitation for wildlife conservation in Barnawapara Wildlife Sanctuary. Non-participant observation, interview schedule, focus group discussion and audio-visual recording were used for primary data collection and research papers, books and internet were used for secondary data collection. The data obtained in the present study shows the impact of changes in the infrastructural conditions of every household after rehabilitation, which also includes the opinions of the displaced families regarding those changes.